Analisis Putusan Mahkamah Konstitusi Nomor 62/PUU- XXII/2024 Tentang Penghapusan Presidential Threshold - Lona Puspita; Raditya Pramana (Normative Jurnal Ilmiah Hukum, 2026)
The Presidential Threshold is the minimum threshold for the percentage of seats obtained in the House of Representatives (DPR) or the percentage of national valid votes that must be met by political parties to be able to propose presidential and vice-presidential candidates. This provision was first implemented in the 2004 Election and was later regulated in Article 222 of the Election Law Number 7 of 2017. This rule is considered to limit democracy and reduce the constitutional rights of political parties and citizens, thus giving rise to debate regarding its suitability with the principle of popular sovereignty in the 1945 Constitution. The problems studied include 1) How are the judges' considerations in the Constitutional Court decision Number 62/PUU-XXII/2024 concerning the Abolition of the Presidential Threshold. 2) What is the legal impact of the decision on the election system in Indonesia. This study aims to determine the judges' considerations in the Constitutional Court decision Number 62/PUU-XXII/2024 concerning the Abolition of the Presidential Threshold and how the decision impacts the election system in Indonesia. The results of this study indicate that: 1) The Constitutional Court considers the Presidential Threshold to be discriminatory, reduces the openness of political competition, and contradicts the principles of morality, rationality, and constitutional justice. This decision marks an important milestone after similar requests were repeatedly rejected. 2) As a result, all political parties can now nominate presidential and vice-presidential candidates without a threshold, although it has the potential to create many candidate pairs and vote fragmentation. The increase in the number of presidential candidates has the potential to extend the election stages, increase the administrative burden on organizers, and increase the risk of political polarization in society.